Padeki Korru Perspektif Hukum Islam - Erna, Siti; Kibtiyah, Muhimatul; Madid, Izzul; Yanto, Supri (Balai Diklat Keagamaan Surabaya, 2021)
This study was based on the tradition of the Sumba people touching their noses when meeting, commonly called Padeki Korru, carried out against people of the same sex or the opposite sex and has been carried out from generation to generation. The purpose of this study is to find out the views of Islamic law regarding the adat tradition of Padeki Korru. This study used a qualitative approach, with 12 sources of the population of West Sumba who were Muslims, non-Muslims, and Muallaf. This research shows that the Padeki Korru Tradition is a forbidden tradition, because it is out of the sharia provisions in the prohibition of touching non-mahrams. When viewed from the point of being a form of religious tolerance and avoiding gossip that is feared will lead to conflict, the researcher directs this to the second level of emergency, namely only in a state of urgency is allowed to practice traditions